Laparoscopic treatment of giant renal cystic echinococcosis. (January 2016) - Shahait, Mohammed; Saoud, Ragheed; El Hajj, Albert
Summary: Hydatid disease is a parasitic infestation caused by the larval form of the cestode Echinococcus granulosus . Isolated renal involvement is quite rare. Surgery is the mainstay of treatment and is classically performed through an open approach with kidney-sparing when feasible. The case of a 33-year-old male patient who underwent laparoscopic unroofing of a giant renal hydatid cyst is described herein.